Validating Domains and Plans for Temporal Planning via Encoding into Infinite-State Linear Temporal Logic - Cimatti, Alessandro; Micheli, Andrea; Roveri, Marco (Proceedings of the AAAI Conference on Artificial Intelligence, 2017)
Temporal planning is an active research area of Artificial Intelligence because of its many applications ranging from roboticsto logistics and beyond. Traditionally, authors focused on theautomatic synthesis of plans given a formal representation of thedomain and of the problem. However, the effectiveness of suchtechniques is limited by the complexity of the modeling phase: it ishard to produce a correct model for the planning problem at hand. In this paper, we present a technique to simplify the creation ofcorrect models by leveraging formal-verification tools for automaticvalidation. We start by using the ANML language, a very expressivelanguage for temporal planning problems that has been recentlypresented. We chose ANML because of its usability andreadability. Then, we present a sound-and-complete, formal encodingof the language into Linear Temporal Logic over predicates withinfinite-state variables. Thanks to this reduction, we enable theformal verification of several relevant properties over the planningproblem, providing useful feedback to the modeler.